2021
DOI: 10.3390/mi12080928
|View full text |Cite
|
Sign up to set email alerts
|

Novel Blood Clot Retriever for Ischemic Stroke

Abstract: Stroke is the second leading cause of death in the world. Ischemic stroke, caused by the blockage of intracranial arteries, accounts for approximately 80% of strokes. Among this proportion, acute ischemic stroke, usually caused by the sudden formation of blood clots, can cause fatal blockages in arteries. We proposed a unique blood clot retriever for the treatment of acute ischemic stroke, and conducted a series of tasks, including design, computer simulation, prototyping, and bench testing, for the proof of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…It uses high-resolution encoders, high-torque motors, and advanced algorithms for achieving high accuracy. The linear movement and rotation of the hypotube were powered by the linear motor stage, whereas the vertical distance between the laser and target surface was controlled by the server motor to reach the optimal laser focal depth [ 47 ]. The stent design was laser-cut onto a 2.0 mm hypotube based on the coded geometry converted from CAD/CAM.…”
Section: Methodsmentioning
confidence: 99%
“…It uses high-resolution encoders, high-torque motors, and advanced algorithms for achieving high accuracy. The linear movement and rotation of the hypotube were powered by the linear motor stage, whereas the vertical distance between the laser and target surface was controlled by the server motor to reach the optimal laser focal depth [ 47 ]. The stent design was laser-cut onto a 2.0 mm hypotube based on the coded geometry converted from CAD/CAM.…”
Section: Methodsmentioning
confidence: 99%
“…As this information can be commercially sensitive, many authors have been forced to reconstruct the geometry through imaging techniques such as optical microscopy or micro-computer tomography (micro-CT) [ 13 15 , 19 ], which might add substantial uncertainty. To model the superelastic behaviour of Ni-Ti, the constitutive law from Auricchio and Taylor [ 31 ] is universally used [ 14 16 , 19 25 , 27 , 28 , 32 34 ], with this model now available as a built-in option in several commercial software packages such as Abaqus, ANSYS and COMSOL Multiphysics [ 35 ]. However, this constitutive model presents challenges as it requires up to 15 independent parameters to be determined [ 36 ].…”
Section: Review Of Computational Modelling Of Nickel-titanium Endovas...mentioning
confidence: 99%
“…Given the significant nonlinearities that are encountered due to the presence of large deformations and complex interactions, the use of explicit solver [13,15,16,[19][20][21][22][23] is preferred over implicit approaches [24][25][26] when modelling Ni-Ti devices. However, explicit solution schemes are conditionally stable, and many studies have applied generic criteria to ensure quasi-static conditions, which require the ratio of kinetic energy to internal energy to be kept below 5% [16,21,27], with additional numerical damping added if required [22].…”
Section: Review Of Computational Modelling Of Nickel-titanium Endovas...mentioning
confidence: 99%
“…(1) age ≥ 18 years; (2) first-episode IS patients with new lesions and no old lesions confirmed by cranial computed tomography (CT) scan and/or cranial magnetic resonance imaging (MRI); (3) patients admitted within 2 weeks of symptom onset; (4) all patients were treated conservatively. The exclusion criteria were as follows: (1) patients with cardioembolic stroke or hemorrhagic stroke, the diagnosis of which being made according to the established diagnostic criteria [20,21]; (2) patients receiving intravenous thrombolysis and/or endovascular treatment, which are time-sensitive interventions, and their clinical presentations and prognoses are distinct from medical management [22,23]; (3) patients complicated with autoimmune diseases, malignant tumors or mental diseases; (4) patients with incomplete data. A total of 926 patients with non-cardioembolic IS were consecutively enrolled, and they followed up until November 2020.…”
Section: Patients Enrollment and Study Designmentioning
confidence: 99%
“…Ischemic stroke (IS) is one of the most common and prevalent stroke subtypes, accounting for more than 80% of patients diagnosed with stroke [1]. Data from the Global Burden of Disease study demonstrated that 77.19 million people had IS in 2019, including 7.63 million new-onset IS cases, and an additional 3.29 million mortalities worldwide [2].…”
Section: Introductionmentioning
confidence: 99%